The Effect of Kahoot-Assisted Discovery Learning Model on Science Learning Interest and Outcomes - Widiadnyani, Kadek; Margunayasa, I Gede; Wibawa, I Made Citra (Universitas Pendidikan Ganesha, 2025)
The implementation of the Kurikulum Merdeka in Natural and Social Sciences (IPAS) learning in elementary schools still faces obstacles, such as conventional teaching methods, low student engagement, and limited media and experimental facilities. This impacts low interest and learning outcomes, exacerbated by the lack of learning innovation. This study analyzes the effect of the Kahoot-assisted Discovery Learning model on the interests and learning outcomes of fifth-grade elementary school students. The method used was a quasi-experiment with random sampling, involving experimental and control groups. Data were collected through questionnaires and tests, then analyzed using the MANOVA test. The results showed that Kahoot-assisted Discovery Learning had a significant effect on students' interests and learning outcomes (sig. 0.001 < 0.05). This model increases learning interest (0.012 < 0.05) through interactive and exploratory learning and improves learning outcomes (0.001 < 0.05) by strengthening conceptual understanding and critical thinking skills. Although effective, the implementation of this model requires infrastructure support and teacher readiness to utilize technology. Overall, Kahoot-assisted Discovery Learning is an innovative alternative to improve the quality of science learning in elementary schools.